Financial feasibility analysis, small business farm beef cattle livestock in Gorontalo District - Amir Halid; Muhammad Muhtar; Sri Yusnani Mokodompit (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
The objectives of this research are: 1) analyze the responses of farmers on small business farm beef cattle livestock in Gorontalo District, 2) analyze the feasibility of small business farm beef cattle livestock in Gorontalo District, 3) analyze the estimated increase of beef cattle production in Gorontalo District. The research method that used is survey method. The data analysis used in this research are descriptive analysis, feasibility analysis, and forecasting analysis. The result of this research showed: 1) The development of beef cattle business is an industry in the field of agribusiness with no limited. Beef cattle farmers said this business could give a huge profits. It can be seen from people welfare that increased, this business does not require a large cost from the technical point of view (cost of facilities and infrastructure), 2) Based on financial analysis aspect of beef cattle livestock is feasible to develop. 3) The result of forecasting analysis can be seen that there will be increased production for the Year 2017-2019 at all intervals except at 1-2cows. Keyword: Financial Feasibility, Beef Cattle, Agribusiness